1996
DOI: 10.1007/bf01411481
|View full text |Cite
|
Sign up to set email alerts
|

Brain energy metabolism in the acute stage of experimental subarachnoid haemorrhage: Local changes in cerebral glucose utilization

Abstract: An experimental model was used to investigate acute alterations of cerebral metabolic activity in rats subjected to subarachnoid haemorrhage (SAH). Haemorrhages were produced in anaesthetized animals by injecting 0.3 ml of autologous, arterial nonheparinized blood into the cisterna magna. Control rats received subarachnoid injections of mock-cerebrospinal fluid to study the effect of sudden raised intracranial pressure, or underwent sham operation. Three hours after SAH rats were given an intravenous injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 49 publications
0
13
1
Order By: Relevance
“…Indeed, comparable findings of normal-to-elevated high-energy phosphate and glucose concentrations and reduced glucose utilization, indicative of decreased metabolic rates, have been reported in injured hemispheres following cold lesions, 4,27 fluidpercussion trauma, 11 and subarachnoid hemorrhage that is possibly due to blood products. 7 In addition, glycogen accumulation that is found in the perihematomal white and gray matter in our model and after a variety of experimental injuries is analogous to that observed under conditions that reduce metabolism, such as hypothermia and anesthesia. 35 Increases in carbohydrate substrate concentration in tissue following ICH may be due to the perihematomal plasma protein accumulation that we previously described in this model.…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, comparable findings of normal-to-elevated high-energy phosphate and glucose concentrations and reduced glucose utilization, indicative of decreased metabolic rates, have been reported in injured hemispheres following cold lesions, 4,27 fluidpercussion trauma, 11 and subarachnoid hemorrhage that is possibly due to blood products. 7 In addition, glycogen accumulation that is found in the perihematomal white and gray matter in our model and after a variety of experimental injuries is analogous to that observed under conditions that reduce metabolism, such as hypothermia and anesthesia. 35 Increases in carbohydrate substrate concentration in tissue following ICH may be due to the perihematomal plasma protein accumulation that we previously described in this model.…”
Section: Discussionmentioning
confidence: 64%
“…SAH was induced in 12 rats (Groups III and IV) by administering 300 lL of autologous blood into the subarachnoid space via the cisterna magna. Details of the procedure have been published previously (d'Avella et al, 1990(d'Avella et al, , 1993(d'Avella et al, , 1996Germanò et al, 1992Germanò et al, , 1994Germanò et al, , 1998bGermanò et al, , 2000Germanò et al, , 2002Germanò et al, , 2007Imperatore et al, 2000). Briefly, the atlanto-occipital membrane was exposed through a midline occipital incision.…”
Section: Sah Surgical Proceduresmentioning
confidence: 99%
“…This neurological injury has been ascribed mainly to ischemic phenomena, occurring either during the initial bleeding episode or as a consequence of macro-and microvascular alterations, which are presumably able to set in motion a global brain dysfunction at different levels (d'Avella et al, 1990(d'Avella et al, , 1996Delgado et al, 1986;Doczi, 1985;Doczi et al, 1986;Germanò et al, 1992Germanò et al, , 2000Jackowski et al, 1990;Johshita et al, 1990;Sasaki et al, 1985Sasaki et al, , 1986Siesjo, 1992aSiesjo, , 1992bZuccarello and Anderson, 1989). Therefore, detailed knowledge about the pathobiology of SAH is critical to develop new treatment strategies; pathophysiological and experimental data together have significant implications both for the management of SAH patients and for investigating the rationale of new pharmacological approaches.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…3,12,15,16,19,20,24 However, the mechanism of the reduction in CBF and cerebral metabolism is not yet clearly understood, particularly the primary process. Previous studies have indicated that CBF reduction is due to an elevation in ICP, metabolic reduction due to disturbance in brainstem-mediated O 2 uptake, or metabolic reduction due to the direct effects of subarachnoid blood.…”
mentioning
confidence: 98%